Analisis Katalisator Kinerja Keberlanjutan Perusahaan untuk Menciptakan Green Strategy pada Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia - Hippy, Mohammad Zubair; Imran, Supriyo; Taan, Hapsawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The purpose of this study is to analyze various factors that influence Corporate Sustainability Performance in creating a green strategy for companies in the agricultural sector, particularly Crude Palm Oil (CPO) companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach using secondary data from 11 Crude Palm Oil (CPO) agricultural companies during the 2021–2024 period, resulting in a total of 44 data observations. Data analysis was conducted using multiple regression with panel data. The results show that institutional ownership, independent commissioners, Return on Assets (ROA), and Debt to Equity Ratio (DER) jointly have a significant effect on Corporate Sustainability Performance in creating a green strategy for agricultural CPO companies listed on the Indonesia Stock Exchange, with a coefficient of determination of 40.6367%. The remaining 59.3633% is explained by other variables not examined in this study, such as firm size, managerial ownership, firm age, environmental performance, and corporate social responsibility disclosure policy. Partially, the findings reveal that institutional ownership has a positive but insignificant effect, independent commissioners have a negative but insignificant effect, Return on Assets (ROA) has a positive and significant effect, and Debt to Equity Ratio (DER) has a negative and significant effect.